The Understanding of Household Livelihood Diversity on Production Forest Areas: A Preliminary Survey on Social Studies - Fajar Julian Santosa; Widiyanto Widiyanto; Dwiningtyas Padmaningrum; Cahyo Wisnu Rubiyanto (Universitas Lambung Mangkurat, 2024)
Forest resources play an essential role in supporting the livelihoods of forest farming households. Households in this area depend heavily on forest-related activities as a source of income and livelihood. However, forest farming households are often faced with various challenges and uncertainties due to climate change, market fluctuations, limited access to land ownership, lack of infrastructure and technological support, and developments in socio-economic conditions that change the values and structure of people's lives. This study is a preliminary survey as an initial process of collecting information and data before carrying out the primary research. This preliminary survey aims to gain an initial understanding of the diversity of forest farmer household livelihoods. Data was collected through a rapid study of 30 households in Gandu Village. Then, data was identified according to information needs and planning the next steps. The results of this study show that forest farming households in Gandu Village diversify their livelihoods in both the agricultural and non-agricultural sectors. The diversity value in the non-agricultural sector shows an average figure of 2.1, which means that each household does not only depend on one source of income. However, they will diversify the number of livelihoods in the amount of 2.1 to meet their household's living needs. The findings of this preliminary survey can become initial data and contribute to further research.